Odyssey : Self Reflection / Faculty of Art & Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
REQASENI XV is an event that is meant to showcase the artworks and designs made by the students from the Faculty of Art and Design. The groups that are showcasing their artworks are from Graphic Design and Fine Art. The work of Graphic Design students are more towards rebranding, redesigning existing designs, and also creating new designs for companies, businesses, and events by utilising the use of technology. As for Fine Art students, the artworks are more on contemporary arts and studying the media dimensions as the main consideration in producing artwork.